Analysis of terrain effects on the interfacial force distribution at the hand and forearm during crutch gait. Issue 4 (1st October 2016) - Rogers, Emma; Leineweber, Matthew J.; Andrysek, Jan
ABSTRACT: Forces transferred to the upper body during crutch use can lead to both short-term and long-term injuries, including joint pain, crutch palsy, and over-use injuries. While this force transmission has been studied in controlled laboratory settings, it is unclear how these forces are affected by irregular terrains commonly encountered during community ambulation. The purpose of this study was to determine the effects of walking speed and uneven terrain on the load magnitude, distribution, and rate of loading at the human-crutch contact surfaces. Our results show that the rates of loading were significantly increased with higher walking speeds and while negotiating certain irregular terrains, despite there being no apparent effect on the peak force transmission, suggesting load rate may be a more appropriate metric for assessing terrain effects on crutch gait. Furthermore, irrespective of the type of terrain and walking condition, the largest compressive forces were found to reside in the carpal-tunnel region of the hand, and may therefore be a primary contributor to carpal-tunnel injury.